Global Research Trends in Irritable Bowel Syndrome: A Bibliometric and Visualized Study - Zhang, Tai; Ma, Xiangxue; Tian, Wende; Zhang, Jiaqi; Wei, Yuchen; Zhang, Beihua; Wang, Fengyun; Tang, Xudong (Frontiers in Medicine, 2022)
Background There are about 10–23% of adults worldwide suffering from irritable bowel syndrome (IBS). Over the past few decades, there are many aspects of uncertainty regarding IBS leading to an ongoing interest in the topic as reflected by a vast number of publications, whose heterogeneity and variable quality may challenge researchers to measure their scientific impact, to identify collaborative networks, and to grasp actively researched themes. Accordingly, with help from bibliometric approaches, our goal is to assess the structure, evolution, and trends of IBS research between 2007 and 2022. Methods The documents exclusively focusing on IBS from 2007 to 2022 were retrieved from the Science Citation Index Expanded of the Web of Science Core Collection. The annual productivity of IBS research, and the most prolific countries or regions, authors, journals and resource-, intellectual- and knowledge-sharing in IBS research, as well as co-citation analysis of references and keywords were analyzed through Microsoft Office Excel 2019, CiteSpace, and VOSviewer. Results In total, 4,092 publications were reviewed. The USA led the list of countries with the most publications (1,226, 29.96%). Mayo Clinic contributed more publications than any other institution (193, 4.71%). MAGNUS SIMREN stood out as the most active and impactful scholar with the highest number of publications and the greatest betweenness centrality value. The most high-yield journal in this field was Neurogastroenterology and motility: the official journal of the European Gastrointestinal Motility Society (275, 6.72%). Gastroenterology had the most co-citations (3,721, 3.60%). Keywords with the ongoing strong citation bursts were chromogranin A, rat model, peptide YY, gut microbiota, and low-FODMAP diet, etc. Conclusion Through bibliometric analysis, we gleaned deep insight into the current status of literature investigating IBS for the first time. These findings will be useful to scholars interested in understanding the key information in the field, as well as identifying possible research frontiers.